How the microbiome challenges our concept of self - Rees, Tobias; Bosch, Thomas; Douglas, Angela E. (PLOS Biology, 2018)
Today, the three classical biological explanations of the individual self––the immune system, the brain, the genome––are being challenged by the new field of microbiome research. Evidence shows that our resident microbes orchestrate the adaptive immune system, influence the brain, and contribute more gene functions than our own genome. The realization that humans are not individual, discrete entities but rather the outcome of ever-changing interactions with microorganisms has consequences beyond the biological disciplines. In particular, it calls into question the assumption that distinctive human traits set us apart from all other animals––and therefore also the traditional disciplinary divisions between the arts and the sciences.